(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the factors responsible for poor drug compliance to anti-diabetic therapy among diabetic patients. Study Design: Cross-Section Study Place and Duration of Study: This study was conducted at the Ayub Teaching Complex, Abbottabad from April 2022 to July 2022. Materials and Methods: In Patients and outpatient who were already diagnosed with type 1 and type 2 diabetes were included in study. Newly diagnosed, pregnant females, Unconscious, terminally ill patients and patients with mental and physical disabilities were excluded from study. Non probability purposive sampling technique was applied for data collection. The data was analyzed in SPSS version 21. Results: In present study 277 diabetic patients were recruited from different medical units. The mean age of the sample was recorded as 58.2 ±12. Fifty percent were male and 49.8 % were female. Majority of patients (58%) belong too urban areas. Most of the patients (55%) were uneducated and 74.5% were dependent on their families. Overall, 44.4% have underlying different comorbidities. Hypertension was the most common comorbidity recorded. 90 patients (32.4%) were noncompliant to anti-diabetic therapy. The most frequent reason for noncompliance was financial constrains among diabetic patients. Conclusion: We have concluded that the comorbidity is devastatingly high in group with non-adherent to anti diabetic medicines. Most common reason for non-compliances is financial constraints. Easily availability of anti-diabetics and procurement by government increases compliance in diabetic individuals. Educations of diabetic individuals especially who are taking medicine in injectable or combination can improve overall compliance to anti-diabetics.